The Derivation of a Design Matrix for a Foot-mounted Inertial Pedestrian Navigation using Invariant Observer Approach - A. A. Rahman; N. S. M. Khairi; K. Abdulrahim (Penerbit Universiti Teknikal Malaysia Melaka, 2024)
Indexed by MyCite